The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Optical Microlithography XXI 2008
DOI: 10.1117/12.772116
|View full text |Cite
|
Sign up to set email alerts
|

Pixelated phase mask as novel lithography RET

Abstract: Novel RET-Pixelated Phase Mask (PPM) is proposed as a novel Resolution Enhancement Technique (RET). PPM is made of pixels of various phases with lateral dimensions significantly smaller than the illuminating radiation wavelength. Such PPM with a singular choice of pixel dimensions acts as a mask with variable phase and transmission due to radiation scattering and attenuation on pixel features with the effective intensity and phase modulated by the pixel layout. Key properties of the pixelated phase masks, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In particular, the use of sub-resolution assist features and pixelated phase masks requires thick mask scattering and polarization effects to be accurately modeled for acceptable lithographic patterning. 18,19 Recently, several papers proposed methods to capture these effects in a fast and efficient way. 20,21 The forward and inverse lithography problem formulation outlined in this paper must be extended to take into account thick mask effects.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of sub-resolution assist features and pixelated phase masks requires thick mask scattering and polarization effects to be accurately modeled for acceptable lithographic patterning. 18,19 Recently, several papers proposed methods to capture these effects in a fast and efficient way. 20,21 The forward and inverse lithography problem formulation outlined in this paper must be extended to take into account thick mask effects.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that this technology can be used to eke out significantly more performance from steppers of a given generation. Figures 17 and 18 briefly describe this; this is also described in detail elsewhere [7]. Fig.…”
Section: Silicon Validationmentioning
confidence: 97%
“…Moreover, technologies such as "pixilated-phase masks" [5] and the need for "computational scaling" [6] further fuel the need for increasing computing resources for advanced process nodes. The introduction of server farms and hardware accelerated OPC has eased the computational challenge, but the growing cost and complexity of OPC is still paramount.…”
Section: Growing Complexity Associated With Scaling In Low K 1 Regimementioning
confidence: 99%